Conjugated Polymer Actuators and Devices: Progress and Opportunities. Issue 22 (25th March 2019) - Melling, Daniel; Martinez, Jose G.; Jager, Edwin W. H.
Abstract: Conjugated polymers (CPs), as exemplified by polypyrrole, are intrinsically conducting polymers with potential for development as soft actuators or "artificial muscles" for numerous applications. Significant progress has been made in the understanding of these materials and the actuation mechanisms, aided by the development of physical and electrochemical models. Current research is focused on developing applications utilizing the advantages that CP actuators have (e.g., low driving potential and easy to miniaturize) over other actuating materials and on developing ways of overcoming their inherent limitations. CP actuators are available as films, filaments/yarns, and textiles, operating in liquids as well as in air, ready for use by engineers. Here, the milestones made in understanding these unique materials and their development as actuators are highlighted. The primary focus is on the recent progress, developments, applications, and future opportunities for improvement and exploitation of these materials, which possess a wealth of multifunctional properties. Abstract : Advances in the development and understanding of conjugated polymer actuators are reviewed, highlighting important developments in the field in the past decades while focusing on current progress and future challenges to deliver "artificial muscles" that can operate in air with high strain, force, and efficiency, and that are responsive, robust, processable, and suitable for mass production.